Giełdowy rynek instrumentów pochodnych w Polsce – szanse i zagrożenia dla zintegrowanego rozwoju - Śpiewak, Tomasz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
W pracy przedstawiona została analiza wybranych aspektów zarządzania ryzykiem w przedsiębiorstwie w świetle zachodzących procesów transformacji społeczno-gospodarczej na przełomie XX i XXI wieku w Polsce. W takich warunkach niezbędna jest budowa efektywnego systemu zarządzania ryzykiem w przedsiębiorstwie, ukierunkowanego na tworzenie wartości. Niezbędne dla rozwoju systemów zarządzania ryzykiem w polskich przedsiębiorstwach jest zwiększenie dostępności narzędzi ograniczania ryzyka oraz podwyższenie poziomu wiedzy na temat tych instrumentów. W świetle zachodzących przemian społeczno-gospodarczych, wdrażanie systemów zarządzania ryzykiem jest warunkiem koniecznym utrzymania, a także poprawy pozycji konkurencyjnej polskich przedsiębiorstw. Rozwój rynku instrumentów pochodnych jest niezbędny z punktu widzenia utrzymania konkurencyjności polskiego rynku w kontekście integracji z Unią Europejską. Dostępność szerokiego wachlarza instrumentów pochodnych dla podmiotów gospodarczych stanowi niezbędny warunek upowszechniania systemów zarządzania ryzykiem, a w konsekwencji poprawy ich pozycji rynkowej. W świetle zachodzących przemian społeczno-gospodarczych, wdrażanie systemów zarządzania ryzykiem jest warunkiem koniecznym utrzymania lub poprawy pozycji konkurencyjnej polskich przedsiębiorstw.

The market of derivative instruments is the youngest segment of the Polish financial market. On the floors of the Stock Exchange in Warsaw derivatives debuted on 16 January 1998, thus almost after 7 years of the operation of the Polish public market. An analysis of the development of this market segment for the last 10 years can incline us to formulate several equivocal conclusions. On the floors of the Stock Exchange in Warsaw in the years 1998-2010, there appeared both futures contracts, index units and financial options. One must give credit to some attempts to differentiate the arrangement of basic instruments that are available to investors; they include shares, indexes, currencies, and interest rates. Similarly, it is impossible not to notice dominance of the derivative market quoted on the floor of GPW SA over the share market in relation to the turnover value. All this evidences without any doubt that development of the exchange market of derivative instruments in Poland is proceeding. On the other hand, however, one should not forget about the phenomena that can evidence occurrence of some weaknesses in development of the said instruments on the regulated markets. Such weaknesses may include, for example, a slow pace of derivative development except for futures contracts for WIG20. Another threat for development of the Polish regulated market of derivative instruments is the structure of the market participants with the dominance of individual investors, which, in connection with dominance of futures contracts for index WIG20 in the turnover, means that transaction on GPW SA are primarily of the speculative character. A barrier for development of the derivative instruments market may be an opinion, which burdens it, that such instruments are the riskiest instruments of the financial market, responsible for escalation of the crisis on the global financial markets. Investments on the capital market are associated with risk. It is suggested erroneously, however, that risk is included in the market itself. It must be stressed that risk depends on the behaviour of a person who realizes an investment. We must remember, however, that the strongest development catalyst of the regulated market of derivative instruments in Poland is possibilities that they give. Derivative instruments may be the construction basis of hedging strategies, which in the past constituted the main premise for development of the regulated derivative market on the global stock exchanges, starting since the 1970s. The specific construction of derivative instruments makes them the most popular tool used in the comprehensive financial engineering, first of all, in construction of investment strategies. Moreover, the said instruments may be used in arbitrage strategies created on the border between the futures market and the cash market. To sum up, the development level of the regulated market of derivative instruments in Poland should be considered as too low. Except for indexed futures contracts (the 4th place among European stock exchanges in relation to the turnover value) the exchange market is featured by a low level of development in relation to differentiation of the offered instruments and their liquidity. Further development of the Polish market of derivative instruments may, in a perspective of several years, facilitate creation of an extended platform of risk management instruments, used both by exchange investors and by businesses.
Keywords: instrumenty pochodne; zarządzanie ryzykiem; transformacja; derivatives; risk management; transformation